Yemeni Crisis 2021 in Al-Arabiya.Net and Irna Arabic Website: A Critical Discourse Analysis Study - Rahman, Farhan Muzhaffar; Abubakar, Irfan (Fakultas Adab dan Humaniora, Universitas Islam Negeri Syarif Hidayatullah Jakarta, 2024)
This study aims to uncover the ideological forms, tendencies, and media interests of Al Arabiya.net and the Islamic Republic News Agency (IRNA) Arabic in their coverage of the 2021 Yemen crisis. The research analyzes news text discourse using Norman Fairclough's critical discourse analysis model, which comprises three dimensions: text analysis, discourse practice, and social practice. The data for this study comes from three Al Arabiya news articles and three IRNA Arabic news articles published between July and December 2021. The research employs a qualitative descriptive method and literature review. The findings reveal that the news texts from Al Arabiya.net and IRNA Arabic exhibit distinct ideological forms and biases. Regarding the 2021 Yemen crisis, the Al Arabiya.net texts demonstrate a negative bias towards the Houthi group while supporting the Yemeni government led by Abdrabbuh Mansur Hadi. Conversely, the IRNA Arabic texts show a negative bias towards the United States, Israel, and the Saudi-led Arab coalition, which has been militarily involved in the Yemen conflict since 2015. The IRNA Arabic texts display sympathy towards the Houthi group and argue that the Arab coalition's actions in the Yemen conflict have worsened the crisis.